Finding Narnia : the story of C.S. Lewis and his brother - Mcalister, Caroline; Jessica Lanan (Illustrator) (New York)
Before C.S. Lewis wrote The Chronicles of Narnia, he was a young boy named Jack who spent his days dreaming up stories of other worlds filled with knights, castles, and talking animals. His brother, Warnie, spent his days imagining worlds filled with trains, boats, and technology. One rainy day, they found a wardrobe in a little room next to the attic, and they wondered, What if the wardrobe had no end? Years later, Jack began to think about what could be beyond that wardrobe, and about a girl named Lucy and her siblings. This picture book biography introduces the beloved creator of The Chronicles of Narnia to a new generation of children who see hidden magic in the world around them
Keywords: Lewis, C. S. (Clive Staples), 1898-1963: Specifies the primary subject, C.S. Lewis, including his full name and birth and death years